Theses Completed at the Department of Library Science, Istanbul University: a Bibliography (1985-1994) - Neslihan Uraz (Türk Kütüphaneciliği)
This paper lists, in chronological order, bibliographie descriptions of undergraduate com-pletion and graduate (master's and doctoral) theses completed at the Department ofLibrary Science of İstanbul University from 1985 to 1994.